Lexical template morphology : change of state and the verbal prefixes in German - Maylor, B. Roger (Studies in language companion series, 2002)
While there have been many attempts in the literature to account for the semantics and syntax of individual German(ic) prefixes, this is the first time that the prefixes have been analysed in a unified way and a framework established that is capable of relating the prefixes to each other and to other areas of the grammar. The templates provide the means whereby a State/Change of State feature interacts with Figure and Ground arguments to generate prefixed verbs, noun- and adjective-incorporating verbs, and oblique case marking on the complements of simplex verbs and adjectives.